Hyaluronan Regulates Cell Behavior: A Potential Niche Matrix for Stem Cells - Mairim Alexandra Solis; Ying-Hui Chen; Tzyy Yue Wong; Vanessa Zaiatz Bittencourt; Yen-Cheng Lin; Lynn L. H. Huang (Biochemistry Research International)
Hyaluronan is a linear glycosaminoglycan that has received special attention in the last few decades due to its extraordinary physiological functions. This highly viscous polysaccharide is not only a lubricator, but also a significant regulator of cellular behaviors during embryogenesis, morphogenesis, migration, proliferation, and drug resistance in many cell types, including stem cells. Most hyaluronan functions require binding to its cellular receptors CD44, LYVE-1, HARE, layilin, and RHAMM. After binding, proteins are recruited and messages are sent to alter cellular activities. When low concentrations of hyaluronan are applied to stem cells, the proliferative activity is enhanced. However, at high concentrations, stem cells acquire a dormant state and induce a multidrug resistance phenotype. Due to the influence of hyaluronan on cells and tissue morphogenesis, with regards to cardiogenesis, chondrogenesis, osteogenesis, and neurogenesis, it is now been utilized as a biomaterial for tissue regeneration. This paper summarizes the most important and recent findings regarding the regulation of hyaluronan in cells.